Bereavement care immediately after perinatal loss in health care facilities: a scoping review protocol. Issue 3 (15th March 2022) - Roberts, Lisa R.; Sarpy, Nancy L.; Peters, Judith; Nick, Jan M.; Tamares, Shanalee
ABSTRACT: Objective: This scoping review will summarize what is known about formal and informal perinatal bereavement care guidelines used in health care facilities before discharge, and map the mental health outcomes of parents against characteristics of the guidelines. Introduction: Conflicting evidence for bereavement care guidelines, the lack of randomized controlled trials and experimental studies, and older synthesized information with a limited focus or population make synthesis complex. A scoping review will help determine the breadth and depth of the literature. Inclusion criteria: Sources pertaining to bereavement care guidelines used in health care facilities immediately after perinatal loss (miscarriage, stillbirth, or neonatal death) and measuring parents' mental health outcomes will be included. Sources relating to family members other than parents, perinatal loss occurring outside of a health care facility, and physical care guidelines will be excluded. Methods: The proposed review will be conducted using the JBI methodology for scoping reviews. The team will consider quantitative and qualitative studies, practice guidelines, case reports, expert opinions, systematic reviews, professional organization websites, and gray literature. Databases to be searched will include CINAHL, PsycINFO, SocINDEX, Cochrane Library, Embase, MEDLINE, and Web of Science. The earliest empirical study found (1976) will serve as the starting date limit. After pilot testing, the two-step screening process (titles and abstracts, then full-text articles), data will be extracted, collated, and presented in narrative form as well as in tables and diagrams. The results will provide facilities with a broad view of bereavement care to support grieving parents' mental health.